Quantification of mixed chimerism allows early therapeutic interventions - Merzoni,Jóice (2014)
Hematopoietic stem cell transplantation is the curative option for patients with myelodysplastic syndrome; however, it requires a long post-transplantation follow-up. A 53-year-old woman with a diagnosis of myelodysplastic syndrome underwent related donor allogeneic hematopoietic stem cell transplantation in July 2006. Three months after transplantation, a comparative short tandem repeat analysis between donor and recipient revealed full chimerism, indicating complete, healthy bone marrow reconstitution. Three years and ten months after hematopoietic stem cell transplantation, the patient developed leukopenia and thrombocytopenia. Another short tandem repeat analysis was carried out which showed mixed chimerism (52.62%), indicating relapsed disease. A donor lymphocyte infusion was administered. The purpose of donor lymphocyte infusion is to induce a graft-versus-leukemia effect; in fact, this donor's lymphocyte infusion induced full chimerism. Successive short tandem repeat analyses were performed as part of post-transplantation follow-up, and in July 2010, one such analysis again showed mixed chimerism (64.25%). Based on this finding, a second donor lymphocyte infusion was administered, but failed to eradicate the disease. In September 2011, the patient presented with relapsed disease, and a second related donor allogeneic hematopoietic stem cell transplantation was performed. Subsequent short tandem repeat analyses revealed full chimerism, indicating complete bone marrow reconstitution. We conclude that quantitative detection of mixed chimerism is an important diagnostic tool that can guide early therapeutic intervention.